HUBUNGAN KEKUATAN OTOT LENGAN DAN BAHU DENGAN AKURASI SERVIS ATAS BOLA VOLI PADA TEAM DI SMPN 3 SEPOTONG - Syahrizan Syahrizan; Saripin Saripin; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, problem in this research is Is there a link arm and shoulder muscle strength with service accuracy on volleyball in extracurricular student at SMPN 3 Piece. The method used is the method of correlations, which can be used to compare the results of measurements of two different variables in order to determine the degree of association between these variables. The population in this study were students of SMPN 3 A piece that follows the extracurricular activities amounted to 25 people. The sampling technique used is total sampling so that the sample in this study there were 25 students. From the calculation of correlation values can be seen that the large value of relationship strength arm and shoulder muscles with service accuracy on volleyball in extracurricular student at SMPN 3 Piece is 0.619 with rtabel value = 0.396, it means rhitung = 0.619> rtabel = 0.396 and it can be said that There is a significant correlation of the arm and shoulder muscle strength with service accuracy on volleyball in extracurricular student at SMPN 3 Piece. After the correlation number obtained, further testing the hypothesis by using t-test Significance formula. From the results of the calculation are known t = 3.78, while ttabel with df = n-2 = 25-2 = 23 at 95% confidence level is 1.714. Thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) that